PENGARUH KOMPENSASI TERHADAP KINERJA ANGGOTA DPRD KABUPATEN KAMPAR - Nursadri Nursadri; Auzar Ali (Jurnal Riset Manajemen Indonesia, 2019)
Research aims to determine the effect of compensation on the performance of DPRD Kampar Regency. Sampling was done by cencus method so that the number of samples in this study were 45 peoples. Data analysis carried out by simple linear regression model and hypothesis testing carried out by the t test at the rate of 5%. Based on the result of the study it can be concluded that compensation has a significant effect on the performance of DPRD Kampar Regency. Correlation coeficient (r) is obtained at 0,922. This gives the meaning that the variable compensation very has a strong relationship with performance of DPRD Kampar Regency.